Analysis of Factors Related to Speech Delay in Preschool Children in Paud Mampang Prapatan District - Aisyiah, Aisyiah; Wowor, Tommy J.F; Rahmah, Wafika (International Journal of Midwifery and Health Sciences, 2023)
Background: Pre-school age children should be given stimuli such as carrying out motorized activities that are trained to get stimulation for all aspects of the child's development and prevent developmental disorders in children. In essence, speaking is an aspect of a child's development that starts from birth. Speech Delay is a tendency where children have difficulty expressing desires or feelings to other people, such as not being able to speak clearly, and lack of mastery of vocabulary which makes the child different from other children his age Purpose: The aim of this research is to analyze the factors that influence speech delay in pre-school age children in PAUD Mampang Prapatan District Methods: The research method used is Descriptive Analysis using Chi Square test data analysis. The sampling technique will be carried out using the Non Random Sampling technique. The research instrument consisted of the KPSP questionnaire, parental knowledge, frequency of gadget use and parenting patterns. Result: The research results showed that there was a relationship between the frequency of gadget use and speech delay (p value 0.051), there was a relationship between parenting patterns and speech delay (p value 0.033) and there was a relationship between parental knowledge and speech delay (p value 0.002). Conclusion: Therefore, the participation of health workers, especially nurses, is needed in studying and analyzing the incidence of speech delay in the aggregate of preschool-aged children